Critically Reveal The Dimensions of Damage From Unauthorized Use of Personal Data: Study of Decision Number 78/Pid.Sus/2024/PN. Tng - Putra, Tegar Islami; Fibrianti, Nurul; Fakhis, Adinda Zeranica Putri; Mohammad Raziq Fakhrullah (The Digest: Journal of Jurisprudence and Legisprudence, 2024)
Unauthorized use of personal data can cause harm to personal data subjects. In its mandate, Decision Number 78/Pid.Sus/2024/PN Tng provides a general outline of the potential harm that may occur to personal data subjects. However, the decision does not specifically explain the forms of loss and its impact on personal data subjects. This research critically discusses the forms of crimes causing harm and their impact on personal data subjects' damage due to unauthorized use of personal data in Decision Number 78/Pid.Sus/2024/PN Tng. The research employs the Library Research method, also known as Legal Research, which focuses on analyzing primary and secondary legal materials based on existing literature. The findings indicate that several general regulations in Indonesia address the crime of unauthorized use of personal data, including Law Number 24 of 2013, Law Number 1 of 2024, Law Number 14 of 2008, and Law Number 27 of 2022. Meanwhile, Decision Number 78/Pid.Sus/2024/PN Tng outlines the damage to personal data subjects resulting from unauthorized use of personal data, with this study revealing various impacts of damage both materially and non-materially.